A historical perspective on the introduction of laparoscopic basic surgical training in the Caribbean and factors that contribute to sustainability of such training. (December 2019) - Parker, Mike; Ramdass, Michael J.; Cawich, Shamir; Fa Si Oen, Patrick; Rosin, David
Abstract: Objective: To report the development of minimally invasive training courses and workshops in the Caribbean and specifically the establishment of the Basic Surgical Skills Course of the Royal College of Surgeons of England (RCSEng) in Trinidad with respect to their value toward Surgical laparoscopic or minimally invasive training in the Caribbean. Design: & Methods: The literature written on laparoscopy in the region was reviewed and in particular that related to the minimally invasive training courses provided over the period 2004 to 2019 and the development of laparoscopic surgical training described from a historic perspective. The factors that contribute to sustainability of courses were identified. Results: Laparoscopic surgical training courses were sporadically introduced into the Caribbean over the period 2004 to 2019 in countries including Barbados, Curacao, Guyana, St. Lucia, Jamaica and Trinidad & Tobago. These were timed and closely related to the establishment of the Caribbean College of Surgeons (CCOS) with the help of the Royal College of Surgeons of England. However, the only certified course introduced was the Basic Surgical Skills (BSS) course of the RCSEng into Trinidad in 2012. This has now been established as a recognised overseas centre by the RCSEng and provides the Intercollegiate BSS course annually forming a solid basis for trainees to learn safe surgical and laparoscopic skills prior to commencing formal surgical training. This has resulted in the sustainable development of minimally invasive training in Trinidad in particular. Conclusion: Laparoscopic skills courses and workshops have been established in the Caribbean for 15 years beginning circa. 2004 to 2019 and have grown in number and locations throughout the Caribbean. The RCSEng and the CCOS have been instrumental in the development process. Of note, the only recognised overseas training centre for Basic Surgical Skills Course was established in Trinidad & Tobago with the support of the RCSEng and seems to be the main contributor to the successful, regular maintenance of these and other minimally invasive courses in General Surgery, ENT, Gynaecology and other fields on an annual, sustainable basis. Highlights: Formal laparoscopic training in the Caribbean has been slow to become established. Lack of resources has been a major component. Skills courses have been varied, intermittent and sporadic. A Royal College of Surgeons of England skills course has been established in Trinidad. Trinidad has become a recognised center due to the BSS.